Complications During Inter-Hospital Transfer of Patients with Acute Ischemic Stroke for Endovascular Therapy. (2nd September 2020) - Sablot, Denis; Leibinger, Franck; Dumitrana, Adrian; Duchateau, Nathalie; Van Damme, Laurène; Farouil, Geoffroy; Gaillard, Nicolas; Lachcar, Marlène; Benayoun, Laurent; Arquizan, Caroline; Ibanez, Majo; Coll, Francis; et al.
Abstract: Purpose : Few data are available on complications occurring during inter-hospital transfer from a primary stroke center (PSC) to a comprehensive stroke center (CSC) for endovascular treatment (EVT) after large vessel occlusion (LVO). Therefore, we prospectively studied data from consecutive patients transferred from our PSC to the next CSC during 4 years to determine the incidence and risk factors of complications during transfer. Methods : This observational, single-center study included consecutive patients transferred from January 1, 2015 to December 31, 2018. During inter-hospital transfer, all medical incidents were systematically recorded. A new complete clinical examination was performed on arrival at the CSC. Results : Among the 253 patients transferred to the CSC during the study period, 68 (26.9%) had one or more complications. In 11 patients (4.3%) these were life-threatening and required emergency intervention by a physician. Baseline characteristics were not different between patients with and without complications, except for the LVO location. Specifically, basilar artery (BA) occlusion was strongly associated with complications during the transport (p < 0.0005). Conclusion: Complications occurred in 26.9% of patients during transfer. Only BA occlusion could predict complication during transfer. Future studies should identify variables to help stratifying patients at high and low risk of complications during transportation.